PENGARUH PROMOSI DAN KEMUDAHAN TERHADAP KEPUTUSAN PENGGUNAAN SISTEM PEMBAYARAN DIGITAL QRIS PADA GENERAZI Z BOJONEGORO - Rahmawati, Laili Nur; Fahrullah, A'rasy (Universitas Negeri Surabaya, 2024)
Advances in digital technology provide convenience for humans. One of the impacts is in the field of digital payment systems, namely QRIS. This study aims to determine the effect of promotion and convenience on the decision to use the QRIS digital payment system for Generation Z in Bojonegoro Regency. This type of research is quantitative research with an associative approach. The sampling method applies non-probability sampling techniques by determining the sample through purposive sampling. The data collection technique used a questionnaire measured on a Likert scale. For data analysis techniques, multiple linear regression is used which is processed with the help of SPSS 24 software. The results of this study indicate that the promotion variable has a positive and significant effect on the decision to use the QRIS digital payment system. Then the convenience variable has a positive and significant effect on the decision to use the QRIS digital payment system. The results of this study indicate that to increase the use of QRIS in Bojonegoro Regency there needs to be more effective promotion and increased ease of use. These two factors have proven significant in influencing the decision to use QRIS among Generation Z.